Conservation and Sustainable Use of PGRFA in Indonesia - Muhamad Sabran; Puji Lestari; Mastur Mastur (Buletin Plasma Nutfah, 2019)
The high diverse of plant genetic resources for food and agriculture (PGRFA) in Indonesia needs to be conserved for sustainable use to achieve food security despite a still growing population. Therefore, database and information system which could add value to the PGRFA have been developed by many international initiatives and conventions which impact to national level. Two international agreements that Indonesia intensively involved to govern access and share the benefit arising from the use of the valuable PGRFA are the International Treaty on Plant Genetic Resources for Food and Agriculture (ITPGRFA) and the Nagoya Protocol of the United Nations Convention on Biological Diversity. Agriculture development in Indonesia, however, is still faced many challenges. This review described and discussed the high biodiversity in Indonesia, utilization and conservation of PGRFA, supporting regulation and policy on PGRFA along with the progress of database and information system. Overall, promoting conservation and the sustainable use of PGRFA is a key goal of various national, regional, and global efforts, initiatives, and agreements governing them for human well-being.